HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA PENYINTAS COVID-19 SELAMA ISOLASI MANDIRI DI WILAYAH DESA KADU - Amelianis Ananda; Eva Marsepa; Ayu Pratiwi (Yayasan Nusantara Hasana Berdikari, 2023)
In the cases that have been confirmed positive for Covid-19 in the Kadu Village Area, Curug District, as many as 140 cases have a psych impact on the Indonesian people, especially in the Kadu Village Area. Covid-19 survivors are particularly prone to anxiety. However, some theories suggest that anxiety can be overcome, one of which is with family support. In this study to find out family support, the level of anxiety in Covid-19 survivors during self-isolation and whether there is a relationship between family support and the level of anxiety in Covid-19 survivors in the Kadu Village Area, Tangerang Regency. This study uses quantitative methods with a cross-sectional design approach. With a total population of 100 Covid-19 survivors using saturated sampling techniques The study obtained family support for Covid-19 survivors during self-isolation in the Kadu Village Area, namely 61 respondents (61.0%), and the level of anxiety in Covid-19 survivors during self-isolation in the Kadu Village Area, namely 37 respondents (37.0%). There is a significant relationship between family support and anxiety levels in Covid-19 survivors during self-isolation in the Kadu Village Area with a coefficient value of 0.828 which means that it has a correlation with the degree of relationship, namely the correlation is very strong and the form of the relationship is positive between the variable level of anxiety and family support. With the results of the chi-square statistical test, p-value = 0.000 was obtained so that the P value <0.05 which means Ha is accepted.